Mekanisme Koping dan Dukungan Keluarga Untuk Mencegah Depresi Pada ANak - Mutiara Putri Adisa; Larasati, TA; Nafisah, Andi (CV. Jasa Sukses Abadi, 2024)
Depression can be caused by a variety of factors, including genetics, mental health, personality, mental health, unemployment, and intelligence. Another common cause of depression in children is lack of family support and proper encouragement. The problem solving process is a useful skill because it is a process of managing mental illness (both external and internal) and requires real effort and effort in the form of suppressing emotions. The problem solving process is the body's response to change, the need to solve problems, and internal and external damage to the mind. Basically, parents have a big role in controlling the growth and development of each child from birth to adulthood. Therefore, parents who ignore their children's needs, especially if the child experiences mental disorders (depression), leave the child empty and without support. Parents can play an advocacy role if they know what to do, including understanding the problems their children face, managing family relationships, and making contributions. a person's level of self-confidence. Mental illness is not something to be ashamed of or hidden, but it is an illness that requires proper treatment. Just like wounds on the hands and feet, wounds in the heart must also be healed. Parents promote good career opportunities for teenagers. The higher the parents' education, the easier it is to help children who are experiencing depression. Supporting children with depression is more than just raising awareness.